Avian-inspired feature-based relative positioning strategy for formation control of multiple unmanned aerial vehicles - Mohamed Yaghoobi, Yousef Jassim Ismail Abdulla (2019)
As a new era of flying machines intersected autonomous and semi-autonomous machines, resulted in the birth of Unmanned Aerial Vehicles (UAVs). It has changed the way human beings travel, transport objects, surveillance execution, emergency response, and other things which time will reveal. Among the various types of UAVs, the Multi-rotor UAVs attained the most attention due to its advantages such as: ease of use, Vertical Take Off and Landing capability, hover flight, and ability to operate in confined area. However, small payload capacity is one of the most discerning disadvantage. Due to limited capability and performance of single Multi-rotor UAVs, interest to overcome this through flight formation and formation control of UAVs has grown significantly over the past few years. One of the key aspects of flight formation is spatial coordination or relative positioning between UAVs flying in close proximity in order to avoid collision and achieve collective operation.